Catalytic cracking of vacuum gas oil by using the aerosol nanocatalysis on new modification catalyst WO3/Si-Zr - Mahdi, Hashim Ali; Abbas, Abdulrahman Khudhur; Sregey, Kudryavtsev (Journal of Petroleum Research and Studies, 2017)
Ukrainian scientists have formulated a new direction in the technology of gas-phase chemical processes – it was called the aerosol nanocatalysis(AnC).The purpose of this research is development of the theoretical foundations of technology aerosol nanocatalysis in the cracking of vacuum gas oil with the use of technology in aerosol nanocatalysis vibration layer of the catalyst system to obtain gasoline and diesel fraction The temperature in the new process is at 250Cº lower than in industrial cracking process , and the amount of catalyst is reduced to a concentration of 2.38 g/m3 reactor . the WO3/Si-Zr – catalyst at conditions of the new technology displayed higher than 99 % of selectivity of light products formation.